DEVELOPMENT, FABRICATION, AND PERFORMANCE EVALUATION OF INDIRECT MULTI-PORTIONED TYPE SOLAR DRYER FOR AGRICULTURAL PRODUCE - HAQ, IJAZ UL; AZAM, HUSNAIN; FIRDOUS, NIDA; MUDDASSIR, MUHAMMAD; SAHAR, AMNA; SALEEM, HAROON; USMAN, MUHAMMAD; MAJEED, ADIL (Innovare Journal of Agricultural Sciences, 2021)
OBJECTIVE: The primary objective of this study was to minimize post-harvest damages and improve the handling of agricultural commodities. The secondary objective was to assess the performance of the dryer by varying inlet velocity of air on temperature, final moisture of the product, drying period, and drying rate METHODS: The present research was carried out for the development, fabrication, and testing of a multi-portioned type solar dryer. The multi-portioned dryer consisted of a collector unit, air storage chamber, drying cabins, and a chimney. A fan assembly was also attached at the inlet of the collector and at the outlet of the drying compartment to control the air velocity and to remove the moist air. RESULTS: The data obtained from the experiments revealed that the maximum temperature elevation of 36.5oC was attained during a no-load test. The results obtained after carrying out load tests revealed that the maximum drying rate of 47 g/hr was achieved at the air inlet velocity of 3.2 m/s. The initial moisture content of 80.50% was brought down to 3.31% in five sunshine hours of 150 gram sliced potatoes. Each portion received air at varying speeds, and it was observed that the portion receiving air at the lowest speed had the maximum temperature. CONCLUSION: The lowest temperature elevation was recorded for the portion receiving air at the highest speed. The dryer was also found to be suitable for the on-field practical application for the drying of perishable commodities.